Disaster Mitigation of Mount Sinabung in Karo District, North Sumatra Province - Barlian, Eri; Dewata, Indang; Umar, Iswandi; Muchtar, Bustari; Anwar, Syafri (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The volcanic eruption of Mount Sinabung has caused the loss of human lives. Hence, for minimizing losses, disaster mitigation is needed. The purpose of this study is to determine the policy directives in mitigating volcanic eruptions of Mount Sinabung. The method to determine the volcano hazard area is the assessment method using geographic information system techniques. Indicators in determining the hazard level are slope, soil type, geology, landform, vegetation, and land use. As for determining the policy directive, this study used the AHP method. The results show that 45 percent of the area is a high risk of the volcano hazard area. From the research, the appropriate policy directive for mitigation is relocating the area further from the volcano.